Beverly Hills cop [videorecording (DVD)] - Brest, Martin, 1951-; Murphy, Eddie, 1961-; Reinhold, Judge, 1957-; Ashton, John, 1948- (Paramount, 2001)
Axel Foley is a brash, street smart Detroit detective who follows the trail of a friend's murderer to the posh surroundings of Beverly Hills. And before Axel gets his man, he gets up to his neck in an international network of smugglers and drug peddlers.